2017
DOI: 10.21597/jist.2017127448
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Seed Yield and Some Agronomical Characteristics of Different Quinoa (Chenopodium quinoa Willd.) Genotypes under Irrigated Conditions

Abstract: Anahtar kelimeler: Kinoa çeşitleri, sulu koşullar, morfolojik özellikler, tohum verimi ABSTRACT: This study was carried out to determine the ripening period, plant height, stem thickness, number of branch per plant, raceme ratio, seed yield, stem yield, biological yield, harvest index, 1000-seed weight, crude protein contents in stem and seed of different quinoa (Chenopodium quinoa Willd.) variety and populations (Cherry Vanilla, French Vanilla, Mint Vanilla, Moqu-Arrochilla, Oro de Valle, Population-China, Q-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Quinoa is generally cultivated for its seeds which are utilized as human food. Thus, a great majority of agronomic studies conducted on the plant includes evaluations on seed performance (Geren et al, 2014;Kir and Temel, 2016;Kir and Temel, 2017;Tan and Temel, 2017a;Tan and Temel, 2018;Casini, 2019). In the studies carried out, it was revealed that seed performances were significantly affected by sowing and harvesting periods and, as a consequence, sowing or harvesting should be carried out at an early or late period (Risi and Galwey, 1991;Aguilar and Jacobsen, 2003;Munir, 2011;Geren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Quinoa is generally cultivated for its seeds which are utilized as human food. Thus, a great majority of agronomic studies conducted on the plant includes evaluations on seed performance (Geren et al, 2014;Kir and Temel, 2016;Kir and Temel, 2017;Tan and Temel, 2017a;Tan and Temel, 2018;Casini, 2019). In the studies carried out, it was revealed that seed performances were significantly affected by sowing and harvesting periods and, as a consequence, sowing or harvesting should be carried out at an early or late period (Risi and Galwey, 1991;Aguilar and Jacobsen, 2003;Munir, 2011;Geren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%